Zbigniew Herbert’s Journeys to the South. A Conversation with Andrzej Franaszek and Francesco Matteo Cataluccio, Conducted by Krystyna Pietrych (during the discussion panel at the 12th ‘Puls Literatury’ Festival in Łódź, 8 December 2018) - Cataluccio, Francesco Matteo; Franaszek, Andrzej; Pietrych, Krystyna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
The topic of a conversation of three literary scholars which took place in the last months of the Zbigniew Herbert Year (2018) is the experience recorded in the poet’s poems and essays of the Mediterranean culture, antiquity as a tool of cognition, an important code as well as the experience of his real journeys to the south of Europe being a kind of dividing line in his literary output and resonating in it.